2016
DOI: 10.1299/mej.16-00408
|View full text |Cite
|
Sign up to set email alerts
|

Study of the efficiency of electrical generator using ferromagnetic powders by electromagnetic analysis

Abstract: Batteries or electric wires are currently in wide use for sensor energy supply. However, industrial waste caused by battery disposal are recognized as a social issue. In addition, the weight of the electric wires supplying electric energy to sensors can reach several kilograms in a car or several hundred kilograms in a passenger aircraft. Thus, reduction of electric wire weight can bring weight saving for a car or a plane. We performed a basic study of development of generation system using ferromagnetic powde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In the electrical generator of this study, it is thought that the behavior of the fluid and the direction of magnetic induction and the magnetic flux greatly contribute to electrical generation [54]. Therefore, the efficiency of the electrical generation was considered by analyzing the magnetic flux distribution of the electromagnetic permanent magnet and using the data to generate a computer simulation [55].…”
Section: Simulating Motion Of Generator Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the electrical generator of this study, it is thought that the behavior of the fluid and the direction of magnetic induction and the magnetic flux greatly contribute to electrical generation [54]. Therefore, the efficiency of the electrical generation was considered by analyzing the magnetic flux distribution of the electromagnetic permanent magnet and using the data to generate a computer simulation [55].…”
Section: Simulating Motion Of Generator Contentsmentioning
confidence: 99%
“…An electromagnetic analysis was conducted by running a computer simulation in ANSYS simulating the distribution state of the magnetic flux density induced in the spike-shaped aggregates of ferromagnetic powders by the permanent magnet. Shirai et al [55] showed that the magnetic flux density concentrates on the tip of the aggregates of the ferromagnetic powders.…”
Section: Simulating Motion Of Generator Contentsmentioning
confidence: 99%